The role of Galectin-3 in modulating tumor growth and immunosuppression within the tumor microenvironment. (3rd June 2018) - Farhad, Mohammad; Rolig, Annah S.; Redmond, William L.
ABSTRACT: The efficacy of cancer immunotherapy is limited, in part, by the multitude of immunosuppressive mechanisms present within the tumor microenvironment (TME). Galectin-3 (Gal-3) is a lectin that contributes to TME immunosuppression and regulates diverse functions including cellular homeostasis and cancer biology. Increased Gal-3 expression during cancer progression augments tumor growth, invasiveness, metastatic potential, and immune suppression, which highlights the potential use of Gal-3 as a therapeutic target capable of modulating anti-tumor immunity. Here, we discuss the mechanisms by which Gal-3 regulates lymphocytes, the role of Gal-3 in lung and prostate tumors, and the contribution of Gal-3 to TME immunosuppression.